DIAGNOSIS OF ARRHYTHMIA DISEASES USING HEART SOUNDS AND ECG SIGNALS - V. Kalaivani (Российский кардиологический журнал)
This paper presents a novel method for the detection of Arrhythmia diseases using both heart sounds and ECG signals. This automated classification and analysis system is aimed to assist the cardiologist to make the diagnosis faster and more efficient. Most of the heart valve disorders are reflected to heart sounds and can be detected through Phono Cardio Gram (PCG) signal analysis. Heart sounds carry information about the mechanical activity of the cardiovascular system. The heart sound segmentation process segments the Phono Cardio Gram (PCG) signal into four parts: S1 (first heart sound),systole, S2 (second heart sound) and diastole. It can be considered as one of the most important phases in the autoanalysis of PCG signals. Systolic and Diastolic time periods of heart sound signals are used to detect the abnormality of heart functions. The Systolic and diastolic time periods are matched with the ECG signals. The interval between two consecutive R peak values in ECG signal is considered as one cardiac cycle. A single cardiac cycle consists of S1, Systole, S2 and Diastole. Both Echocardiogram and Electrocardiogram signals are analyzed for the accurate diagnosing of cardiac vascular diseases.